Violence, betrayal, complicity: a study of apartheid perpetrator narratives - Bloch, Robyn Cassandra (My University, 2018)
This investigation considers the phenomenon of perpetration and its representation in contemporary South Africa. To uncover what is hidden or omitted in these narratives and to understand how writing about violence influences the text and the writer, I critically analyse five recently published books by or about apartheid perpetrators. My first chapter analyses Anemari Jansen’s biography Eugene de Kock: Assassin for the State (2015) by tracking De Kock’s shifting representation over the past 20 years. In my second chapter, which investigates Askari: A Story of Collaboration and Betrayal in the Anti-Apartheid Struggle (2014), I examine writer Jacob Dlamini’s battle to confront black betrayers. Hugh Lewin’s Stones Against the Mirror: Friendship in the Time of the South African Struggle (2011) is the story of how Adrian Leftwich, a fellow anti-apartheid saboteur, stood state witness against Lewin. I analyse white betrayal as premised from a position of privilege. My fourth chapter looks into the autobiography of the apartheid spy Olivia Forsyth, Agent 407: An Apartheid Spy Breaks her Silence (2015). Forsyth absconds from responsibility by writing three contradictory narratives and training her focus on surfaces. Her depiction of black women shows that she plays into the power dynamics of a white madam. Finally, my fifth chapter examines Bridget Hilton-Barber’s Student, Comrade, Prisoner, Spy: A Memoir (2016). Hilton-Barber, I argue, conjures her past and relives it in the present. In doing so, she acts as a witness to her younger self. But her book reveals forms of privilege and whiteness, and thus enacts another kind of betrayal. I conclude that each text employs narrative devices to contend with this contentious material and that the violence of the material causes the writers’ sense of self to fracture
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements of the degree of Doctor of Philosophy Johannesburg, 26 October 2018
Keywords: Political persecution--South Africa; Assassins--South Africa; Political crimes and offenses; Apartheid--South Africa; South Africa--Biography